(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
This article analyzes the artistic interpretation of the theme of social mobility in the novels of the renowned American writer Theodore Dreiser. The study examines the protagonists’ aspirations to climb the social ladder and the moral-ethical consequences of this process in works such as The Financier, Sister Carrie, and An American Tragedy. The concept of social mobility in Dreiser’s work is illuminated within the context of the “American Dream,” linked to economic determinism and the biological instincts of the characters. The paper provides scientific conclusions regarding Dreiser’s depiction of the social environment’s power in determining human destiny and the tragic nature of vertical mobility.